Impact Of Family Physician–Led Interventions On Weight Reduction And Glycemic Control In Patients At Risk Of Type 2 Diabetes: A Systematic Review And Meta-Analysis (The Review of Diabetic Studies, 2025)
Background: Family physicians play a pivotal role in diabetes prevention and management through lifestyle counseling, behavioral modification, and multidisciplinary care. This systematic review and meta-analysis aimed to evaluate the impact of family physician–led interventions on weight reduction and glycemic control among individuals at risk for or diagnosed with type 2 diabetes mellitus (T2DM).Methods: Following PRISMA 2020 guidelines, ten peer-reviewed randomized and quasi-experimental trials were included, spanning 2000–2025. Data were extracted from PubMed, Scopus, Web of Science, and Embase. Outcomes assessed included changes in body weight, body mass index (BMI), glycated hemoglobin (HbA1c), and fasting plasma glucose (FPG).Results: Physician-led interventions integrating dietary education, exercise prescription, and behavioral counseling achieved significant improvements in BMI (mean reduction = 2.3–8.4 kg) and HbA1c (−0.5% to −0.8%). Long-term interventions such as DiRECT and DiaBEAT-it demonstrated sustained weight loss and partial diabetes remission, while multicomponent programs involving interprofessional collaboration enhanced glycemic outcomes. Family- and community-based models were effective in maintaining healthy weight trajectories in children and underserved populations.Conclusions: Evidence supports that family physician–led programs in primary care substantially improve metabolic health, demonstrating scalable, cost-effective potential for T2DM prevention and control. However, heterogeneity in study designs and follow-up durations warrants further large-scale standardized trials.